Modifications to the Endoscopic Approach for Anterior Skull Base Lesions Improve Postoperative Sinonasal Symptoms - Thompson, Christopher F.; Suh, Jeffrey D.; Liu, Yuan; Bergsneider, Marvin; Wang, Marilene B. (Journal of Neurological Surgery Part B: Skull Base, 2014)
Background/Objective Our institution previously showed that patients experience significant postoperative sinonasal symptoms for the first few months after endoscopic transnasal transsphenoidal skull base surgery (eTNTS). Since our initial study we have modified our technique, discontinuing routine resection of the middle turbinate, maxillary antrostomies, and nasoseptal flaps. In this study, we analyze whether these technical modifications decrease postoperative sinonasal morbidity after eTNTS.Methods A retrospective review was performed of 93 consecutive patients who underwent eTNTS at a tertiary academic medical center from August 2011 to August 2012.Main Outcome Measures  Sino-Nasal Outcome Test (SNOT)-20 and SNOT-22 scores preoperatively and after surgery.Results Compared with our previous study, our new cohort experienced a significant improvement (p < 0.05) in SNOT scores for the need to blow nose, runny nose, postnasal discharge, thick nasal discharge, wake up at night, reduced concentration, and frustrated/restless/irritable. Within the new cohort, patients who did not have a nasoseptal flap or middle turbinate resection had less worsening and faster improvement of nasal symptom scores after surgery.Conclusions Preserving normal sinonasal physiology during eTNTS by limiting middle turbinate resections, avoiding unnecessary maxillary antrostomies, and reducing the use of nasoseptal flaps when feasible results in less sinonasal morbidity and more rapid recovery during the postoperative period.
Keywords: skull base; endonasal surgical approach; endoscopic surgery; nasoseptal flap